Pengaruh Local Strongman Di Provinsi Jambi (Studi Kasus Dominasi Zulkifli Nurdin Terhadap Partai Amanat Nasional) - Zakly Ahmad; Aryo Akbar; Adlin Adlin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2020)
The transfer of power from centralization to decentralization has greatly influenced the political climate of every region in Indonesia, the presence of local strongmen is an epidemic in a democratic country. The dynamics that occur have resulted in economic and political domination which has an impact on democratic life. This study uses a literature study approach with data collection techniques derived from online news, books and research related to the discussion. This research aims to explore and explore how the role of Zulkifli Nurdin in polarizing the National Mandate Party in Jambi Province to maintain its image as a local strongman. Zulkifli Nurdin's domination succeeded in making the National Mandate Party as a tool to form his political dynasty in Jambi, this was made up of officials in the National Mandate Party consisting only of his family and cronies